Konsep al-Mutrāfūn dalam QS. Al-Isrā’ Ayat 16: Tafsir Sosial-Ekologis atas Eksploitasi Lingkungan Perspektif Fazlur Rahman - Rofiqur Rahman; Luthviyah Romziana (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to analyze Qur'an Surah Al-Isra’ verse 16 using a thematic exegesis approach and Fazlur Rahman’s double movement theory, and to contextualize it within contemporary environmental exploitation in Indonesia, particularly illegal logging and deforestation. This research employs a descriptive qualitative method with a document-based study, analyzing the Qur'an, classical and contemporary tafsir literature, and relevant environmental studies. The findings reveal that the concept of al-mutrāfīn refers not only to those who live in luxury but also to elites who possess structural power and influence within society. When such power is not accompanied by moral and spiritual responsibility, it leads to collective deviations resulting in social and ecological destruction. In the Indonesian context, the exploitation of natural resources reflects the pattern of al-mutrāfīn, where elite dominance contributes to deforestation, social inequality, and increased ecological disaster risks. Therefore, Surah Al-Isra’ verse 16 contains universal moral principles that serve as a normative framework for understanding the relationship between power, environmental exploitation, and societal collapse. This study highlights the importance of integrating Qur'anic ethical values into natural resource governance to achieve ecological justice and environmental sustainability.